Development of an advanced composite system form for constructability improvement through a Design for Six Sigma process - Lee, Dongmin; Kim, Taehoon; Lee, Dongyoun; Lim, Hyunsu; Cho, Hunhee; Kang, Kyung-In (Journal of Civil Engineering and Management, 2020)
System form is widely used when constructing concrete buildings and structures because it has high productivity and good concrete casting quality compared with traditional hand-set form. However, from a worker’s perspective, system form is still very harsh to handle because of its heavy weight, noise generation, and use of releasing agent, and it also attenuates the productivity of system formwork. Therefore, this study proposes the use of an advanced composite material-based concrete form for workers using a Design for Six Sigma (DFSS) process to improve constructability of system formwork. User requirements are systematically reflected in the technical characteristics of concrete form, and innovative principles are scientifically organized through the DFSS process that mainly consists of quality function deployment and theory of creative problem-solving methods. The proposed composite form showed improved performance in deriving high-quality formwork and worker-friendly working conditions compared with previous system forms. Additionally, this study demonstrated how the DFSS will be a valuable tool for technology development and systematic decision-making in building construction.